Using natricine snakes to test how prey type and size affect predatory behaviors and performance - Gripshover, Noah D.; Jayne, Bruce C. (Frontiers in Behavioral Neuroscience, 2023)
Predation is a complex process for which behavior, morphology, and size of both predator and prey can affect the success and effectiveness of the predator. For predators such as snakes that swallow prey whole, gape ultimately limits prey size, but the behaviors used to select, capture, and consume prey and attributes of the prey can also affect maximal prey size. For example, swallowing live, struggling prey is difficult, but using coiling or envenomation to restrain or kill prey has evolved repeatedly in snakes. To test the potential benefits of these behaviors, we manipulated the type and size of prey, and determined how stereotyped predatory behavior was in a snake species (Liodytes rigida) that uses both coiling and envenomation to restrain and immobilize its formidable prey of crayfish. We also studied a close relative (Liodytes pygaea) that eats fish and salamanders to gain insights into the evolution of these traits. For L. rigida, envenomation of hard-shell crayfish via their soft underside was very stereotyped (100% of feedings). Envenomation of soft-shell crayfish was less frequent (59% of feedings) but became more likely both with increased relative prey size and increased time after molt (hardness). L. rigida coiled more with hard-shell than with soft-shell crayfish (77% vs. 30%). The probability of coiling was unaffected by prey size, but it increased with increased time after molt for the soft-shell crayfish. Liodytes rigida waited to swallow crayfish until they were completely immobile in 75% and 37% of the feedings with hard- and soft-shelled crayfish, respectively. Even with very large vertebrate prey, L. pygaea never used coiling or envenomation, whereas previous studies of L. alleni, the sister species of L. rigida, observed non-lethal coiling without envenomation when eating hard-shell crayfish. For the Liodytes clade of three species, this implies that coiling evolved ancestral to the two crayfish specialists (L. alleni; L. rigida), and envenomation by L. rigida subsequently evolved as an additional means of subduing formidable prey. The proximate benefits observed for coiling and envenomation in L. rigida support the evolutionary scenario that both traits evolved to enhance the feeding performance for more formidable prey.